THE LAGOON OF VENICE : EVOLUTION IN TIME OF THE HYDROGEOMORPHOLOGICAL PROCESSES, IN THE WATERSTREAMS AND THE LAGOON OF VENICE (ITALY) - Marabini, F.; Μερτζάνης Α. (Bulletin of the Geological Society of Greece, 2018)
This work depicts the evolution in time of the hydrogeomorphological processes and the human impact which from the historical era have contributed to the actual configuration of the Lagoon of Venice (northwestern Adriatic sea). Those natural hydrogeomorphological processes, in combination with the intense human interference, have led to the increase in the rate of occurrence of the phenomenon of the high level of tide, a phenomenon known as "acque alte", which is prominent today in the Lagoon area and the complex of the "sand islands" which are formed inside the Lagoon. This work also describes the measures prescribed and taken, according to environmental protection program (Mose), in order to deal more effectively with this undesirable hydrogeomorphological processes in the area o.’*he Lagoon of Venice.